Photocatalytic C-N bond construction toward high-value nitrogenous chemicals - Li, Jie; Liu, Tengyu; Singh, Nittan; Huang, Zhuochun; Ding, Yan; Huang, Jinshu; Sudarsanam, Putla; Li, Hu (Chemical Communications, 2023)
The construction of carbon-nitrogen bonds is vital for producing versatile nitrogenous compounds for the chemical and pharmaceutical industries. Among developed synthetic approaches to nitrogenous chemicals, photocatalysis is particularly prominent and has become one of the emerging fields due to its unique advantages of eco-sustainable characteristics, efficient process integration, no need for high-pressure H2, and tunable synthesis methods for developing advanced photocatalytic materials. Here, the review focuses on potential photocatalytic protocols developed for the construction of robust carbon-nitrogen bonds in discrepant activation environments to produce high-value nitrogenous chemicals. The photocatalytic C-N bond construction strategies and involved reaction mechanisms are elucidated. This review focuses on potential photocatalytic protocols developed for the construction of robust carbon-nitrogen bonds in discrepant activation environments to produce high-value nitrogenous chemicals.